SPEMBERIAN AIR REBUSAN DAUN SIRSAK TERHADHAP PENURUNAN NYERI ASAM URAT PADA PENDERITA GOUT ATRITIS DI WILAYAH KERJA PUSKESMAS DELI TUA TAHUN 2020 - Fakultas Keperawatan DELI HUSADA Deli Tua (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Pain is a common complain with gout. That pain caused increase uric acid level in the elderly. Analgesic which constantly consumed will result in side effect so that needed nonpharmacological therapy. One nonpharmacological therapy to reduce uric acid and pain are Annona Muricata L extract. The purpose of this study was to analyze the effectiveness of Annona Muricata L extract to reduce uric acid and pain on gout patient at puskesmas working area Deli Tua. This research was a pre-experimental pre-post test design and was evolved 30 respondents were given extract Annona Muricata L leaf with Total sapling decrease in gout pain. Respondent drink extract Annona Muricata L leaf twicw a for 3 day drink 3x a day.measuremert of join pain using numeric rating scale. The datas were analyzed by Paired Sample T-test with significance α<0.05. The statistical there is a decrease in gout pain after interventionp-value=0,00(<0,05) Ho rejected Ha received. Which means the influensi of sorsop leaf boiled water on decreasing gout pain patiens with gout athitis.